The Resilient Physician A Pocket Guide to Stress Management - Kelly IV, John D. (Springer International Publishing, 2018)
Written by a veteran clinician for medical practitioners of all disciplines and levels of experience, this concise pocket guide presents a frank discussion about facilitating resiliency in the face of the personal and professional challenges of a medical career. Furthermore, it provides proven techniques and suggestions for stress management aimed at the maintenance of a more successful practice and peaceful life. First defining and elucidating the problems of stress plaguing the field, including burnout, substance abuse and suicide, the bulk of the book presents and discusses ways to combat and master the everyday stress of the "medical marriage," such as engaging mindfulness training, learning to forgive oneself and others, listening to your own body, utilizing time away from medicine, and performing simple acts of kindness and gratitude. Issues surrounding the inevitability of mistakes, the pursuit of perfectionism, happiness and success are then examined and reflected upon, as are stress management considerations from other cultures and literary sources. Equal parts personal and practical, The Resilient Physician is a must-have for any clinician or medical professional seeking better understanding and outcomes when handling the constant demands of this high-stress - but ultimately rewarding - career.